Reception of Knut Hamsun in Romanian and Bulgarian context - Lățug, Diana; Tetimova, Evgenia (Journal for German and Scandinavian Studies / Списание „Германистика и скандинавистика“, 2025)
This article is the first comparative attempt to analyze Knut Hamsun’s reception in Romania and Bulgaria, showing how peripheral cultural positions influence both the interpretation, translation and publication of his work. It summarizes the results of Romanian research and compares them with similar Bulgarian research. This is the first attempt to compare Knut Hamsun’s reception in two countries, centered on two peripheral cultures and neighboring countries. The aim is to show possible similarities and differences between Hamsun’s reception in Romania and Bulgaria and to contribute to the larger topic of Hamsun’s reception in the world.
Keywords: reception; periphery; translations; articles; press